2014
DOI: 10.1080/10286020.2014.898633
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification, and structural elucidation of polysaccharides from Alhagi-honey

Abstract: The polysaccharide extract (PE) of Uyghur medicinal preparation Alhagi-honey was prepared by water extraction and alcohol precipitation method. The purified polysaccharide AP1-1 was obtained from PE by macroporous adsorption resin chromatography, DEAE cellulose chromatography, and Sephadex gel chromatography; the homogeneity and the molecular weight of AP1-1 were determined by gel filtration; and the acid hydrolysis, periodate oxidation, Smith degradation, and NMR analysis were used to analyze the chemical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the strong biological activity of polysaccharides was strongly related to monosaccharide compositions [ 28 ], and the monosaccharide composition of polysaccharides played an important role in further analyzing its physicochemical properties, structure and structure-biological activity. At present, there were many ways to determine the monosaccharide composition, including high performance liquid chromatography [ 29 ], reversed-phase high performance liquid chromatography (HPLC) after pre-column derivatization [ 30 ], high-performance thin-layer chromatography [ 31 ], gas chromatography (GC) [ 32 ], high-performance anion-exchange chromatography [ 33 ], high performance capillary electrophoresis [ 34 ]. In our study, the monosaccharide compositions were measured by GC with good sensitivity, and monosaccharide composition was estimated by comparing retention time (RT).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the strong biological activity of polysaccharides was strongly related to monosaccharide compositions [ 28 ], and the monosaccharide composition of polysaccharides played an important role in further analyzing its physicochemical properties, structure and structure-biological activity. At present, there were many ways to determine the monosaccharide composition, including high performance liquid chromatography [ 29 ], reversed-phase high performance liquid chromatography (HPLC) after pre-column derivatization [ 30 ], high-performance thin-layer chromatography [ 31 ], gas chromatography (GC) [ 32 ], high-performance anion-exchange chromatography [ 33 ], high performance capillary electrophoresis [ 34 ]. In our study, the monosaccharide compositions were measured by GC with good sensitivity, and monosaccharide composition was estimated by comparing retention time (RT).…”
Section: Resultsmentioning
confidence: 99%
“…AHP was extracted and purified using a previously described preparative column chromatography method,27 AHP [MW 47,479 Da, main chain-2,3)‒α‒L-Rhap‒(1,2,6)α‒D‒Manp‒(1,3)‒β‒D‒Galp-(1,3,6) α‒D-Galp‒ (1-, while the side chain is composed of α-D‒Glcp‒(1‒] carbohydrate and protein contents were 99.0% and 0.7%, respectively. OVA and AHP-loaded PLGA nanoparticles (AHPP/OVA) were prepared using a water/oil/water (w/o/w) double emulsion technique 28.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the ratio of the amount of monosaccharide to amount of periodate was nearly 1 : 1 for polysaccharide S-3-1. This proved that the 1,3-linked forms that do not consume periodate were either not present or few in number [28]. The periodateoxidized products of S-3-1 were further reduced, hydrolyzed, and analyzed by GC-MS.…”
Section: Structural Characterization Of S-3-1mentioning
confidence: 99%